1980
DOI: 10.1038/bjc.1980.255
|View full text |Cite
|
Sign up to set email alerts
|

Colony formation by normal and malignant human B-lymphocytes

Abstract: Re(ei v\e(d I I AIarch 1(90 A\(cepted 16 May 1 981) Summary.-A method is described that permits colony formation in culture by B lymphocytes from normal blood and from blood, marrow or lymph nodes of patients with myeloma or lymphoma. The method depends on: (1) exhaustively depleting cell suspensions of T lymphocytes, (2) a medium conditioned by T lymphocytes in the presence of phytohaemagglutinin (PHA-TCM), and (3) irradiated autologous or homologous T lymphocytes. Under these conditions the assay is linear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…When 4 x 105 cells of the 10 marrow preparations of 9 patients were plated, a sufficiently high plating efficiency (0-15-1.0%) was obtained to allow a reliable comparison between test and control assays. This plating efficiency is similar to that reported by Izaguirre et al (1980) but much higher than that reported by Hamburger and Salmon (1977).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When 4 x 105 cells of the 10 marrow preparations of 9 patients were plated, a sufficiently high plating efficiency (0-15-1.0%) was obtained to allow a reliable comparison between test and control assays. This plating efficiency is similar to that reported by Izaguirre et al (1980) but much higher than that reported by Hamburger and Salmon (1977).…”
Section: Discussionsupporting
confidence: 91%
“…Using the modified method developed by Izaguirre et al (1980) human myeloma stem cells could be detected by their ability to form colonies. When 4 x 105 cells of the 10 marrow preparations of 9 patients were plated, a sufficiently high plating efficiency (0-15-1.0%) was obtained to allow a reliable comparison between test and control assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excess of OKT8/Leu-2a+ T cells over OKT4/Leu-3a+ T cells commonly observed in this series is also observed, though less commonly, in reactive lymph nodes, but does not alone imply a reaction by "cytotoxic" T cells against "neoplastic" B cells. Moreover, there is good evidence that the clonogenic components of NHL B cells are, like normal B cells, dependent upon T cell factors, and T cells, for growth (Izaguirre et al, 1980).…”
Section: Phenotypic Heterogeneity In Peripheral Tcellsmentioning
confidence: 99%
“…22,23 Clonogenic methods for B and T lymphocytes were also described. 24,25 Colony formation in culture depends of the presence of bioactive stimulators, colony-stimulating factors or CSF. The rapid development of methods for studying molecules were quickly applied to CSFs.…”
Section: Colonies In Culturementioning
confidence: 99%